Late antenatal care booking and associated factors among pregnant women in Mizan-Aman town, South West Ethiopia, 2021 - Gelila Gashawbeza Battu; Roza Teshome Kassa; Haweni Adugna Negeri; Leul Deribe kitawu; Kassahun Demelash Alemu (Public Library of Science (PLoS), 2023)
Background Antenatal care (ANC) is one of the most important ways to reduce maternal and neonatal morbidity and mortality. According to data from poor countries, the majority of pregnant women attend ANC when they are in their later stages of pregnancy. In this regard, limited information is currently known about the factors that determine ANC scheduling and the type of care for pregnant women in the town of Mizan-Aman in southwestern Ethiopia. Therefore, the purpose of this study was to determine late antenatal care booking and associated factors among pregnant women in the Town. Method The institutional-based cross-sectional study design was conducted in Mizan-Aman town using a systematic random sampling method through structured questions from February 15 to March 25, 2021. The collected data was entered into EPI info-7 which later on, was exported to SPSS version 20 for statistical analysis. Binary and multiple logistic regressions were used to identify associated factors and p-value <0.05 was considered for statistical significance. Results A total of 425 female pregnant women participated, making a 100% response rate. The prevalence of delayed first ANC bookings in this study was 70.0% [95.0%, CI = 65.65-74.35]. Multivariate analysis revealed that unplanned pregnancy [AOR = 2.63, 95% CI: 1.18, 5.85], inappropriate perception of ANC starting time [AOR = 4.1, 95% CI: 1.9, 8.83], pregnant women who were unaware of pregnancy-related danger signs [AOR = 6.76, 95% CI: 2.83, 16.1], and pregnant women who were unaware of service delivery during working hours in the institution [AOR = 0.44, 95% CI: 0.19, 0.98]. Conclusion The current study showed a greater prevalence of delayed ANC beginnings, and the factors for this were having an unplanned pregnancy, lack of awareness about pregnancy danger signs, inappropriate perception of ANC starting time, and pregnant women who were unaware of service delivery during working hours at the institution. Responsible bodies working in maternal and child health care better create awareness of the benefits of early ANC booking and appropriate ANC starting times. Further, each health institution's MCH clinic should deliver the service through working hours.